Decidualized ovarian and rectouterine deep endometriosis disguised as malignancy in the second-trimester of pregnancy: A case report - Lingjie Bao; Ting Wang; Yinping Xiao; Shouxin Gu; Xiaoyu Zhou; Yunxi Zheng; Yun Chen; Xiaofang Yi (Heliyon)
Introduction: Pregnancy is a special time during which some benign hormonally-responsive lesions could grow and mimic malignancy on clinical evaluation and imaging. Though decidualization of ovarian endometrioma has been reported, little is known about decidualization of deep endometriosis. Here we report a case of decidualized bilateral ovarian endometriomas and rectouterine deep endometriosis mimicking as malignant lesions in the second-trimester of pregnancy. Case presentation: A 26-year-old woman at 14 weeks of gestation presented to our hospital for the first time routine examination. Transvaginal ultrasound (TVS) showed bilateral adnexal masses of uneven echo with size 8.7 × 7.3 cm in the left ovary and size 5.5 × 4.8 cm in the right ovary, and another cystic mass with size 3.3 × 3.1 cm at rectouterine pouch. Serial nuclear magnetic resonance imaging (MRI) without contrast media for further evaluation indicated that these newly found pelvic masses were suspected to be ovarian endometrioid carcinoma with a metastasized lesion at rectouterine pouch. Serum CA125 was 56.7 U/L. HE-4 was 73.9 U/L. Considering that potential malignancy imaging had never been detected before pregnancy, multidisciplinary discussion (MDT) with doctors from obstetrics, gynecology, radiology and pathology department was organized at once. Conservative laparoscopic surgery was suggested to determine the pathology first. When removing the ovarian cysts and the lesion at rectouterine pouch, rich papillary nodules inside the capsule were exposed and looked like malignancy. Fortunately, frozen section revealed these lesions to be decidualized endometrioma. This patient recovered well and then went to the department of obstetrics for high-risk pregnancy supervision. Finally, the baby was delivered at 39 weeks by cesarean section because of fetal growth restriction (FGR). Conclusions: Decidualization of endometriomas, especially deep endometriosis during pregnancy brings great challenge for clinical practice. A mature multidisciplinary team shows essential importance during treatment decisions. Early diagnosis of endometriosis before pregnancy help identify malignancy and reduce potential risks of maternal and fetal complications.